Performative Epistemology and the Philosophy of Experimental Biology: A Synoptic Overview - Esposito-Varriale, M (Springer Science and Business Media B.V., 2020)
In his 1995 book, The Mangle of Practice, Andrew Pickering distinguished between representationalist and performative idioms in philosophy of science. While the former describes science as mainly a theoretical enterprise, the latter represents science as a collection of practices. The two perspectives outline two kinds of epistemologies presenting different philosophical concerns. In fact, in a scientific world where entities are not only thought or represented but touched, used, and transformed, the question about their existence does not really matter. What does matter though is to what extent we can extrapolate, from all our experimental material activities, the “real” working of the natural processes. In this chapter, drawing on Pickering s insights, we introduce a particular kind of performative epistemology fit for grasping how experimental biologists produce reliable knowledge. We argue that experimental biology can be mapped through four principal points: constrained action, standardization, epistemic “tightening,” and extrapolation. We show that each point presents its own proper problems, assumptions, and epistemic challenges. All together, the points define what we call the Epistemic Experimental Space (EES), i.e., the space in which experimental knowledge is produced, assessed, and validated. Without the pretention to be exhaustive, we also identify some of the main conditions making experimental knowledge in biology a highly consistent, reliable, and successful epistemic activity. © 2020, Springer Nature Switzerland AG.